Geostatistics Application in 3-D Reservoir Modeling for Calculation of Hydrocarbon Resources, Case Study: North Rembang Area: Aplikasi Geostatistika Dalam Pemodelan Reservoir Tiga Dimensi Untuk Perhitungan Sumberdaya Hidrokarbon, Contoh Kasus di Area Rembang Utara - Ramli, Taufik (Politeknik Harapan Bangsa Surakarta, 2023)
Oil and gas are still indispensable commodities to meet Indonesia's energy needs in the next few decades, even though government policies related to energy transition towards net zero emission have begun to be encouraged. However, the oil and gas requirement is not followed by the availability of reserves or resources owned by Indonesia. The objective of this study is to discover new hydrocarbon resources, through 3-D reservoir modeling using geostatistical method. The geostatistical method is still the best current method to predict the distribution of facies association and reservoir petrophysical properties such as porosity and water saturation. In facies association modeling, a stochastic geostatistical method is used, namely the Truncated Gaussian with Trends (TGS) algorithm. For porosity and water saturation (SW) modeling, the Sequential Gaussian Simulation (SGS) algorithm was applied. The results of 3-D modeling of facies associations, porosity, and water saturation are utilized to estimate gas resources in the North Rembang Area. From the estimation of gas resources, it is recognized that the Rembang Utra Area has accumulated gas resources around 3 TCF.